Dramaturgy of the Written Skin: black Gaúcha Inscrituras and Insurgent Fabulations in Preta Poesia Feminina (2021) by Silvia Duarte - Quadros, Dênis Moura de (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
In a country that has silenced Black voices and burned its archives, the stage has become a living archive, and the skin, a surface of memory. When a Black woman embodies others through her voice, she not only evokes external writings but also reinscribes collective histories in an aesthetic gesture that is inherently political. This analyzes the performance Preta Poesia Feminina (2021), conceived and performed by Silvia Duarte, by the concept of “inscritura,” understood as a performative act of writing inscribed upon the skin, the voice, and the presence of Black women. The investigation seeks to understand how the work, initially presented in a digital environment, articulates body, memory, and ancestry as aesthetic and political practices of enunciation. An analytical-interpretative methodology is employed, grounded in the works of Quadros (2020; 2023), Evaristo (2020), and Martins (2003; 2021), to examine how Black-feminine dramaturgy emerges in the poetic selection, in the vocality of the performer, and in her relationship with the audience. The analysis demonstrates that the scene constructs a collective and insurgent writing, in which the Black feminine body is inscribed as a symbolic surface of resistance and re-existence. It concludes that Preta Poesia Feminina updates a dramaturgy rooted in lived experience and ancestry, projecting a fabulation of self and community into the digital-theatrical space, sustained by the political and affective force of oraliture.